Cold gel-like emulsions of lactoferrin subjected to ohmic heating - Furtado, G. (2018)
Ohmic heating is a technique that has gained increasing attention because of its capacity to produce uniform heating, and claimed electrical influence on the functional and technological properties of treated protein dispersions. The aim of this work was to evaluate the influence of ohmic heating on the properties of cold gel-like emulsions, comparing them with those obtained by conventional heating. The effect of ohmic and conventional heating on physical and structural properties of lactoferrin was also addressed. Ohmic heating treatment resulted in less pronounced aggregation of lactoferrin, when compared to conventional heating. An increase of particle size, turbidity, intrinsic and extrinsic fluorescence values and a decrease of dichroic signal after heat treatment indicated an increase of protein interactions. Emulsions produced from heat-treated lactoferrin showed gel-like behavior which was related to the emulsifying capacity of lactoferrin, combined with the emulsification method and the heat pre-treatment applied to the protein. Rheological and microstructural properties were intrinsically related to the heat treatment of the protein since ohmic heating produced gel-like emulsions with a less rigid structure. These emulsions could be interesting for food applications containing heat-sensitive ingredients.